Compliance-technologies in marketing - Kobielieva, Tetiana; Kocziszky, György; Veres Somosi, Mariann (Wyższa Szkoła Ekonomiczno-Humanistyczna, 2018)
The scientometric analysis of the term "compliance" is used in the article, which is used to denote the organization's continuous efforts to comply with all local and foreign laws, regulations and rules applicable to its activities, including its own internal corporate policies and procedures. For many years, compliance has been emphasized solely in industries that are traditionally tightly regulated, such as health care and financial services. However, after the anti-corruption legislation came into force in Ukraine and Hungary, all industries began to be regulated quite rigidly, and for each legal entity (or division) there was a need for strict monitoring of compliance by industrial enterprises with countless existing laws, regulations and regulations. Ultimately, the essence of a reliable compliance program is not only to avoid investigations, but mostly to shape the ethical environment in which the business will prosper. At present, compliance technologies are increasingly being used in the marketing activities of industrial enterprises.
Keywords: compliance; marketing; program; risks; control; principles; enterprises